# Chebyshev Polynomial The Chebyshev Polynomials of the first kind

Document Sample

```					Chebyshev Polynomial

The Chebyshev Polynomials of the first kind denoted by                           n(x)         =   ; n= 0,1,2,… are

Solutions of the chebyshev’s differential equation:-

   To show that                 n(x)   is a solution of the chebyshev’s differential equation :

n(x)   =                                ; n= 0,1,2,…
`n(x) =                                     )

``n(x) =                                    )+                               )

Now : (1-           )                        )+                                   )

= -                                  +                      )–

Hence        n(x)   is a solution of shebyshevi differential equation

    n(x) can be written as :
n(x) =               (1-                                 (1-        )2 + ….
To verify equation (1) , we use that
n(x) =              )
Let               , so cos
, then n(x) = cos n

Now by DeMoivre’s theorem :
n
(cos               = cos n + i sin n
n
So that n(x) = cos n
Applying the binomial theorem on (cos                                        )2
We get :
n         2
(cos               =         +                                      (i sin                 (i sin )2 +
(i sin )3 +                    (i sin )4 + ……
From this we get that:
n                             n
=                                                (i sin )2 +              (i sin )4
and            =            =1-
n(x)   =          -                (1- ) +         (1-         )2 ….
Now : By equation (1) we can list the first few chebyshev’s polynomials of the first kind
:-
So , To find 0(x) = = 1.
To find 4(x) Put n = 4 in equation (1) we get :-
4(x)   =   -                    (1-     )+               (1-       )2
=       –                 (1-    ) + (1-2x2+x4)
= – 6x2 + 6x4 + 1 – 2x2 + x4
= 8x4 – 8x2 + 1
And so on To find the rest:
2             3
1(x) = x , 2(x) = 2x -1 , 3(x) = 4x -3x
5       3
5(x) = 16x – 20x + 5x
6       4      2
6(x) = 32x – 48x + 18x - 1
7        5      3
7(x) = 64 x - 112x + 56 x – 7x

Note:
1(x) is a polynomial of order (1)

2(x) is a polynomial of order (2)

In general           k(x)   is a polynomial of order (k).

** Generating function for n(x):
The generating function for n(x) is given by :
=                     n(x)

** special values of the chebyshev polynomials n(x) :
(i)      n(1) =                 =         =
(ii)      n(-1) =                   =        =        .
(iii)        2n(0)        =                                      =                 =            =    .
(iv)      2n+1(0) =                        =                   =
=0
In fact we can also user equation (1) to verify these results.
We can also verify the above four result by using the generation function for                                     n(x):

(i)          n(1):     substitute x = 1 in                                =            n(x)

-
n
=                  n(1)t       =>             ==                   tn

n
=>            =              n(1)t          , but         =          tn

So :         tn =                        tn , Now equating the Coefficients of tn we get                   n(x)   = 1.
If we set x = 0 in the generating function we get :-

=               n(0)        , But              =

Hence :                                                       n(0)

Equating the Coefficient, of tn , once when n is even and once when n is odd , we get :

2n(0)   = (-1)n ,          2n+1(0)   =0

(ii)           n(-1)   = (-1)n : to verify this set x = -1 in the generating function we get:
=                n(-1)

                  =                   =>       =           n(-1)

But             =
                                                   n(-1)                                     we get
:
n(-1)   = (-1)n

Rule :       n(-x)   = (-1)n     n(x)

Proof : to prove this rule we using equation (1) and substituting –x we get :

n(-x)   = (-x)n -          (-x)n-2(1-(-x)n-2) +              (-x)n-4(1-(-x) 2)2 - …..

= (-1)n (x)n -           (-1)n-2 xn-2 (1-x2) +                (-1)n-4 xn-4(1-x2)2 - ….

= (-1)n [(x)n -          (-1)-2 xn-2 (1-x2) +                 (-1)-4 xn-4(1-x2)2 - ….]

= (-1)n [(x)n -          xn-2 (1-x2) +                xn-4(1-x2)2 - ….]

So    n(-x)    = (-1)n      n(x)

*** Recurrence Relations for                         n(x):-

(i)   n+1(x)    – 2x     n(x)   +     n-1(x)     =0

(ii)(1-x2)       n(x)   = -n x       n(x)   +n       n-1(x)

To verify these recurrence relations, we use

n(x)   =                            , So Let                   = , so that cos              and   n(x)   = cos(n ).

No to prove (i) :

n+1(x)      – 2x    n(x)   +   n-1(x)   = cos((n+1) )-2cos cos(n ) + cos((n-1) )
= cos(n               ) – 2cos cos(n ) + cos(n

But cos(n           + ) = cos(n )cos( ) – sin(n )sin( )

and cos(n                           cos(n )cos( ) + sin(n )sin( )

So : cos(n      ) – 2cos cos(n ) + cos(n                                                        = cos(n )cos( ) – sin(n )sin( ) –
2cos cos(n ) + cos(n )cos( ) + sin(n )sin( ) = 0

So :        n+1(x)   – 2x          n(x)   +    n-1(x)   = 0 which recurrence relation (i)

To prove recurrence relation (ii) we start with the left hand side:

(1-x2)      n(x)    = (1-x2)               n(x)

= (1-cos2                 cos(n ).            = (sin2 ) (-n sin(n )) . (               )

So (1-x2)          n(x)   = n sin                       ). ---------------- (a)

Now : the Right hand side:

-n x     n(x)   +n        n-1(x)   = -n cos          cos(n ) + n cos ((n-1) )

= -n cos        cos (n ) + n cos                   cos (n ) + -n x         n(x)   +n   n-1(x)

So -n x      n(x)   +n       n-1(x)       = -n x     n(x)   +n    n-1(x)   .-------------------(b)

From (a) and (b) we get recurrence relation (ii):

(1-x2)      n(x)    = -n x         n(x)   +n      n-1(x)

Examples : Evaluate (a)                       2(x)   , (b)       2(x)

If   0(x)   =1 ,     1(x)   = x.

(a) To evaluate 2(x) we use recurrence relation (i):-
2(x) - 2x 1(x) + 0(x) = 0
2
2(x) = 2x – 1

(b) To find 2(x) we use recurrence relation (ii) :-
(1-x2) 2(x) = -2 x 2(x) + 2 1(x) = -2x(2x2-1)+2x = -4x3+2x + 2x = 4x(1-x2)
So       2(x)    =                  = 4x.
**** Orthogonality:

dx =

Examples:
(i)                   dx =                 ((since n=m=0))

(ii)                  dx =               ((since n=m=2))

(iii)                    dx =            ((since n           ))

(iv)                              dx = 0
Since 32x7-56x5+28x3-3x =         3(x)     4(x)

So                      dx = 0 ((since n          ))

3(x): Polynomial of order 3.

3(x) Polynomial of order 4.

3(x)   3(x)                                    AND        odd = 0

```
DOCUMENT INFO
Shared By:
Categories:
Tags:
Stats:
 views: 9 posted: 2/26/2012 language: English pages: 5